Our Battalion : Being Some Slight Impressions of His Majesty's Auxiliary Forces, in Camp and Elsewhere - Raven-Hill, L. (Leonard), 1867-1942 (Salt Lake City, UT : Project Gutenberg, 2010)
"Our Battalion" by L. Raven-Hill is a humorous historical account written in the early 20th century. The book offers insights into the life of volunteers serving in His Majesty's Auxiliary Forces, capturing their experiences during military camps and drills. The story delves into the dynamics of volunteer soldiers, their training, and the challenges they face, while showcasing the camaraderie and camaraderie among the ranks. The narrative unfolds through a series of sketches and anecdotes that provide a vivid portrayal of military life. Characters like the grumpy Sergeant (3z(BTiny,(3y (Benthusiastic junior officers, and recruits with their concerns about drills bring a relatable charm to the text. The book explores themes of duty, eagerness, and the often comical inadequacies of volunteer forces in the face of military expectations. Each chapter encapsulates various situations, from the excitement of early recruits to the chaos of camp life, punctuated by witty commentary on the military system. Overall, "Our Battalion" serves as both an entertaining and insightful reflection of military service and the human spirit within it. (This is an automatically generated summary.)s
Release date is 2010-10-22
E-text prepared by Marcia Brooks, Ross Cooling, and the Online Distributed Proofreading Canada Team (http://www.pgdpcanada.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Caricatures and cartoons -- Great Britain; Armies -- Caricatures and cartoons